1969
DOI: 10.1063/1.1657433
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoelastic Waves in Time-Varying Magnetic Fields. I. Theory

Abstract: Direct calculation of the electric field induced by a timevarying magnetic induction Am.Effect of a timevarying boundary on the sound field in an enclosure. I Substituting this equation into Eq. (C3) then yields an expression identical to Eq. (Cl) indicating that the solution (19) is the correct solution far from the plane z=O.The propagation of microwave magnetoelastic waves in a ferromagnet subjected to pulsed magnetic fields is investigated. In the first part of the theoretical analysis, which is restricted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…The study of magnon-phonon interaction dates back to the 1950s and 1960s, when the strong coupling between spin waves (magnons) and acoustic waves (phonons), as well as the resulting magnetoelastic waves (hybrid magnon-phonon states) have been investigated in both theory and experiments. [36][37][38][39][40][41][42][43] In recent years, with the increasing interests in utilizing phonons as an information carrier for coherent and quantum information processing, [44][45][46][47] magnon-phonon coupled systems have re-emerged as a promising platform for hybrid magnonics. Phonons exhibit very long lifetimes in solid state platform such as silicon, quartz, diamond, aluminum nitride, lithium niobate, etc., which satisfy the require-ments of a large variety of coherent applications.…”
Section: B Magnetomechanics and Magnon-phonon Coupled Devicesmentioning
confidence: 99%
“…The study of magnon-phonon interaction dates back to the 1950s and 1960s, when the strong coupling between spin waves (magnons) and acoustic waves (phonons), as well as the resulting magnetoelastic waves (hybrid magnon-phonon states) have been investigated in both theory and experiments. [36][37][38][39][40][41][42][43] In recent years, with the increasing interests in utilizing phonons as an information carrier for coherent and quantum information processing, [44][45][46][47] magnon-phonon coupled systems have re-emerged as a promising platform for hybrid magnonics. Phonons exhibit very long lifetimes in solid state platform such as silicon, quartz, diamond, aluminum nitride, lithium niobate, etc., which satisfy the require-ments of a large variety of coherent applications.…”
Section: B Magnetomechanics and Magnon-phonon Coupled Devicesmentioning
confidence: 99%
“…At microwave frequencies, this mutual interaction manifests itself in a coupling between spin waves-the fundamental magnetic excitations in this frequency range-and (hypersonic) elastic waves, forming magnetoelastic waves. While this behavior was studied for plane waves in bulk materials decades ago [13][14][15][16][17][18][19][20], magnetoelastic waves in nm-thin films have been studied only much more recently. Most of these studies have focused on the interaction between surface acoustic waves propagating at the interface between a (piezoelectric) substrate and a thin magnetostrictive film with macroscopic dimensions [5,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the existence of measurable effects of timevarying medium properties on propagating waves has already been established in the field of electromagnetism, with theoretical descriptions of media changing smoothly or instantaneously. [20][21][22][23][24][25][26][27] These studies predict that a wave that propagates at varying speed (i.e., in a medium with temporally varying dielectric or magnetic constant) is subjected to a variation in amplitude and oscillation period; additionally, reflected waves are generated at time-discontinuities of the medium, similar to what happens at the spatial interface of two media. Experimental studies 20,28 confirmed the predictions regarding amplitude and frequency changes by observing magnetic waves propagating in media subjected to an externally modulated magnetic field.…”
Section: Introductionmentioning
confidence: 99%